Role of Aquaporins during Teleost Gametogenesis and Early Embryogenesis - Chauvigne, Francois; Zapater, Cinta; Cerda, Joan (Frontiers in Physiology, 2011)
Aquaporins are believed to be involved in homeosmotic mechanisms of marine teleosts. Increasing data suggest that these molecular water channels play critical roles associated with the adaptation of gametes and early embryos to the external spawning environment. In this mini-review, we discuss recent studies suggesting the function of aquaporin-mediated fluid homeostasis during spermatozoa activation and egg formation in teleosts. In addition, we address the potential role of water channels in osmosensing and cell migration during early embryonic development.